Liver resection in patients with eight or more colorectal liver metastases. Issue 1 (January 2015) - Viganò, L.; Capussotti, L.; Majno, P.; Toso, C.; Ferrero, A.; De Rosa, G.; Rubbia‐Brandt, L.; Mentha, G.
<x xml:space="preserve">Abstract</x> Background Patients with large numbers of colorectal liver metastases (CRLMs) are potential candidates for resection, but the benefit from surgery is unclear. Methods Patients undergoing resection for CRLMs between 1998 and 2012 in two high‐volume liver surgery centres were categorized according to the number of CRLMs: between one and seven (group 1) and eight or more (group 2). Overall (OS) and recurrence‐free (RFS) survival were compared between the groups. Multivariable analysis was performed to identify adverse prognostic factors. Results A total of 849 patients were analysed: 743 in group 1 and 106 in group 2. The perioperative mortality rate (90 days) was 0·4 per cent (all group 1). Median follow‐up was 37·4 months. Group 1 had higher 5‐year OS (44·2 versus 20·1 per cent; P < 0·001) and RFS (28·7 versus 13·6 per cent; P < 0·001) rates. OS and RFS in group 2 were similar for patients with eight to ten, 11–15 or more than 15 metastases (48, 40 and 18 patients respectively). In group 2, multivariable analysis identified three preoperative adverse prognostic factors: extrahepatic disease (P = 0·010), no response to chemotherapy (P = 0·023) and primary rectal cancer (P = 0·039). Patients with two or more risk factors had very poor outcomes (median OS and RFS 16·9 and 2·5 months; 5‐year OS zero); patients in group 2 with no risk factors had similar survival to those in group 1 (5‐year OS rate 44 versus 44·2 per cent). Conclusion Liver resection is safe in selected patients with eight or more metastases, and offers reasonable 5‐year survival independent of the number of metastases. However, eight or more metastases combined with at least two adverse prognostic factors is associated with very poor survival, and surgery may not be beneficial.